Pheromone cCF10 inhibits the antibiotic persistence of Enterococcus faecalis by modulating energy metabolism - Zhu, Li; Yang, Xiaobo; Fu, Xinyue; Yang, Panpan; Lin, Xiaoli; Wang, Feng; Shen, Zhiqiang; Wang, Jingfeng; Sun, Feilong; Qiu, Zhigang (Frontiers in Microbiology, 2024)
Introduction Bacterial resistance presents a major challenge to both the ecological environment and human well-being, with persistence playing a key role. Multiple studies were recently undertaken to examine the factors influencing the formation of persisters and the underlying process, with a primary focus on Gram-negative bacteria and Staphylococcus aureus (Gram-positive bacteria). Enterococcus faecalis (E. faecalis) is capable of causing a variety of infectious diseases, but there have been few studies of E. faecalis persisters. Previous studies have shown that the sex pheromone cCF10 secreted by E. faecalis induces conjugative plasmid transfer. However, whether the pheromone cCF10 regulates the persistence of E. faecalis has not been investigated. Methods As a result, we investigated the effect and potential molecular mechanism of pheromone cCF10 in regulating the formation of persisters in E. faecalis OG1RF using a persistent bacteria model. Results and discussion The metabolically active E. faecalis OG1RF reached a persistence state and temporarily tolerated lethal antibiotic concentrations after 8 h of levofloxacin hydrochloride (20 mg/mL) exposure, exhibiting a persistence rate of 0.109 %. During the growth of E. faecalis OG1RF, biofilm formation was a critical factor contributing to antibiotic persistence, whereas 10 ng/mL cCF10 blocked persister cell formation. Notably, cCF10 mediated the antibiotic persistence of E. faecalis OG1RF via regulating metabolic activity rather than suppressing biofilm formation. The addition of cCF10 stimulated the Opp system and entered bacterial cells, inhibiting (p)ppGpp accumulation, thus maintaining the metabolically active state of bacteria and reducing persister cell generation. These findings offer valuable insights into the formation, as well as the control mechanism of E. faecalis persisters.